Curative Resection of Pancreatic Adenocarcinoma with Major Venous Resection/Repair is Safe Procedure but Will not Improve Survival - Hamidian Jahromi, Alireza; Jafarimehr, Elnaz; Dabbous, Hany M; Chu, Quyen; D’Agostino, Horacio; Shi, Runhua; Wellman, Gregory P; Zibari, Gazi B; Shokouh-Amiri, Hosein (JOP. Journal of the Pancreas, 2014)
Objective To evaluate the safety and survival benefit of combined curative resection (CR) of the pancreas and major venous resection in the management of borderline resectable pancreatic adenocarcinoma. Methods In this IRB approved retrospective cohort study, patients who had pancreatic surgery (n=274) between 1998-2012 were reviewed. One hundred and seventy-five patients had malignant causes, of which 119 underwent CR. One hundred and two patients who did not require venous resection/repair (Group-I) were compared with 17 patients who had major vascular involvement (portal-vein/superior-mesenteric-vein) and underwent a vascular resection/repair (Group-II) during the CR. Demographics, operative and follow-up data were reviewed. Result Type of the operations were: standard Whipple (n=53), pylorus-sparing-Whipple (n=41), total pancreatectomy (n=11), and distal pancreatectomy (n=13). In Group-II, venous involvement was excised and primarily repaired (n=12), or repaired using other veins (n=4) or a synthetic patch (n=1). Group-II had a significantly larger tumor size and more perineural invasion and peripancreatic soft tissue involvement (P<0.05). While complication rate, margin status, and duration of stay were not different between the groups, the median-overall-survival was higher for Group-I (15.34 months) than Group-II patients (7.18 months) (P=0.003). Conclusion Pancreatic CR requiring intra-operative venous resection/repair is feasible and safe, but the survival of the patients who have pancreatic adenocarcinoma with venous involvement is poor irrespective of a successful venous resection. Image: Overall survival of patients with and without vascular resection.